Evaluasi Kepuasan Pengguna Aplikasi Tapp Market Menggunakan Metode EUCS (End User Computing Satisfaction) - Asti Shofi Damayanti; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Tapp Market is a new online shop established in 2013 in Finland and entered Indonesia in 2015, therefore required an evaluation for Tapp market in order to compete with its predecessor. Evaluation was conducted by using End User Computing Satisfaction (EUCS) method where consists 2 variables; accuracy and timeliness. There were 4 indicators of variable contentand 1 indicator of timeliness. Data was obtained from the number of samples of 100 respondents using questionnaires. From the result of variable of accuracy was very High category with the resulting value was 76.6% which means the users felt Very Satisfied to Tapp Market application if measured from this variable. The result of variable of timeliness was Low category with the value obtained was 50.0% which means the users felt satisfied toward Tapp Market application if measured from this variable. The recommendation given in this research is variable with Low category a Timeliness need to improve service quality, so that its category can reach very High category in order to increase user satisfaction of Tapp Market application.